Pengaruh Good Corporate Governance, Ukuran Perusahaan, Profitabilitas, dan Leverage terhadap Manajemen Laba - Prisila Damayanty; Mutiara Ayuningtyas; Oktaviyanti Oktaviyanti (Neolectura, 2022)
This study was conducted with the aim of analyzing the effect of institutional ownership, audit committee, firm size, profitability, and leverage on earnings management. The population used in this study were all manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2016 – 2018. The sample in this study was 44 companies using the purposive sampling method. Hypothesis testing in this study using multiple linear regression analysis. The results showed that institutional ownership, audit committee, firm size, ROE and DER had no effect on earnings management, while ROA had a positive effect on earnings management. Simultaneously institutional ownership, audit committee, firm size, ROA, ROE, and DER affect earnings management.